Influence of Spherical Aberration on the SNR in Single-Beam Laser Doppler Velocimeter for Remote Measurement - Lanjian Chen; Jian Zhou; Chongbin Xi; Xiaoming Nie; Shilong Jin (IEEE Access, 2023)
In contrast to those deployed on land vehicles, the single-beam Laser Doppler velocimeter (LDV) used for velocity acquisition on airborne vehicles requires a focusing transmitter. The effects of spherical aberration in focusing transmitters on the distant velocity measurement of single-beam Laser Doppler velocimeters are demonstrated in this work. The calculations of the numerical simulations based on the generated theories and the subsequent experiments are in agreement with the theoretical analyses. The impact of spherical aberration on the signal-to-noise ratio (SNR) of single-beam Laser Doppler velocimeters is explained. Also illustrated is the generalized analysis for single-beam Laser Doppler velocimeters equipped with complex optics. An efficient approach for evaluating and advancing the SNR performance of single-beam Laser Doppler velocimeters used for distant velocity measurement is demonstrated. Works in this paper pave way for the design of airborne LDV.